Narrativas de los docentes frente al rol en la prevención de la conducta suicida en adolescentes de un colegio público en Barrancabermeja. (2023)
This research was conducted with the objective of analyzing the narratives of teachers regarding their role in the prevention of suicidal behavior in a public school in the city of Barrancabermeja. Therefore, this study was designed under an exploratory descriptive qualitative approach using narratives, for this purpose, in-depth interviews were conducted with the participants, who were selected by means of a non-probabilistic convenience sampling technique.